Analysis of Constructed Swamp Forest Vegetation as A Phitoremediation Agent in Coal Mining, South Kalimantan - Citra Rahmatia; Iwan Hilwan; Irdika Mansur; Ihsan Noor (Department of Forest Resources Conservation and Ecotourism - IPB University, 2019)
Coal mining activities could potentially interfere with the environment. One of the environmental disturbances in coal mining activities is theformation of acid mine drainage (AMD). AMD management can be done passively through the construction of swamp forest. The constructed swampforest system uses organic material in the form of cow manure which serves as a growing plants’ medium. Phytoremediation is an attempt to usevplant species in the accumulation of heavy metals. This study was aimed to know the AMD management system passively and identify the diversity ofplants in artificial swamp forests. Purposive sampling method with a sample size of 2 x 2m in 10 plots/compartments was used to identify the plantdiversity in constructed swamp forest. The observation was made both before and after AMD flowed. Constructed swamp forest consist of 6compartments (2 sediment pond compartments and 4 swamp compartments). The results of the vegetation analysis found that before the AMD flowed,21 species are still capable growing naturally in constructed swamp forest, however, it became 15 after the AMD flowed. Cyperus iria, Fimbristylisgriffithii, Scirpus juncoides, Ludwigia hyssopifolia, Cyperus platystylis and Monochoria vaginalis are six dominant species that can be used asphytoremediation agent in constructed swamp forest.Keywords: Acid Mine Drainage, constructed swamp forest, phytoremediation